Corporate Social Performance and the Likelihood of Bankruptcy: Evidence from a Period of Economic Upswing - Florian Habermann; Felix Bernhard Fischer (Journal of Business Ethics, 2021)
The paper aims to investigate the effects of corporate social performance (CSP) on bankruptcy likelihood in times of economic upswing. This is important because prior related literature focused on data containing times of economic crises. We measure bankruptcy likelihood with the Altman Z score and CSP with Refinitiv ESG scores. By applying static panel data regressions and instrumental variable regressions on a sample of 6696 US-firm-year observations from 2010 to 2019 our main findings are: (i) In contrast to existing research, the level of firms' CSP seems to have no (positive) effect on the likelihood of bankruptcy during times of economic upswing. (ii) Increasing a firm's CSP in times of economic upswing leads to a rise in bankruptcy likelihood. We conclude that the positive effects of CSP on stakeholder relationships fail to materialize in flourishing business environments. The costs of increasing CSP, thus, exceed their immediate positive effects and raise bankruptcy likelihood. However, as they reduce financial default risk in subsequent crises, CSP investments can be seen as a balancing measure. Our findings bear implications for scholars, practitioners, and policymakers.
Keywords: G30; G33; G34; M14; 300; Corporate social performance; Bankruptcy; ESG ratings; Altman Z score; Stakeholder theory; Corporate financial performance